Effect of Helium Plasma Irradiation on Microstructures and Mechanical Properties of Tungsten - Aidar Kengesbekov; Bauyrzhan Rakhadilov; Zarina Satbaeva; Yedilzhan Kambarov (Advances in Materials Science and Engineering)
The paper presents the results of the study of tungsten surface structure modification under helium plasma irradiation. It is revealed that during irradiation of samples, surface modification in the form of relief development as a result of irradiation is observed. X-ray phase analysis showed that no new phases of the W system were found after irradiation, only an increase in the intensity of diffraction lines was observed. There are significant differences in the microstructure of tungsten depending on the temperature of helium plasma irradiation in the above range. It is assumed that the cause of defects is the extremely low solubility of helium in tungsten. Metallographic analysis has shown that at irradiation of tungsten samples in time modes 1 and 1.5 hours, the degree of relief development is not high in comparison with the tungsten sample irradiated in the 0.5-hour mode. The greatest increase in surface roughness of the sample irradiated for 1 hour was registered, which is associated with the formation of small cracks, bubbles, and pores in the surface layer. At the same time, in the samples irradiated for 1.5 hours, the surface of which is characterized by chaotically located protrusions and depressions of various shapes, the roughness parameter Ra was 0.0603 μm. It was found that at temperature regimes T = 1200°C and T = 1500°C, the microhardness of tungsten increases by 10% and 11%, respectively.